The Use of Second Person Pronouns in Shakespeare’s Tragedy of Hamlet and Macbeth - Putranti, Adria Indah (Universitas Sanata Dharma, 2015)
This article concerns on the use of second person pronouns thou and you in Shakespeare’s Tragedy of Hamlet and Macbeth. Throughout the history of English language, second person pronouns have undergone many changes until they become only one form you. In the earlier period, the distinction between thou and ye was in a matter of the number of people being addressed. However, in early modern English, the use of second person pronouns did not depend only on the number of people, but also on the power and solidarity relations. Dealing with its changes, the use of second person pronouns thou and you in Shakespeare’s plays is interpreted in this article. Results show that Shakespeare’s plays provide a different view of the use of these pronominal forms. Nevertheless, Shakespeare actually follows the rule of pronominal forms dictated by society, yet some cases show inconsistency. The inconsistency refers to the switching between thou and you. It indicates that something emotionally happens among the characters which can be observed through their conversations.